Aesthetice of Adul Qaher Al- Jarjani"s Metaphorical Style (Journal of Hama University, 2019)
Metaphor is a tool of imagination that shows us the world unlike what we have entrusted; a renewable world in which the word acquires endless connotations, and metaphor acquires an additional symbolism, thanks to imaginative photography at the intersection of levels between different universes and by the combination of elements, Life. This study found its misguidance in the views of Abdul-Qaher al-Jarjani (471 e) on the rhetorical method of borrowing by talking about the concept of deception and its manifestations.The relation of metaphor to the imagination from the perspective of Al-Jarjani is illustrated by the following aspects:- First, the similarity and homogeneity that is between the things that usually connect, and the imagination between them and imagine them in various situations; single and composite, and here shows the talk of the prosecution and the talk of forgetting analogy in the metaphor in the views of Abdul-Jerjani as these concepts to clarify the process of homogenization of the photography Fantasy through the metaphor mechanism.- Second: To give life to non-functioning things, and to give them a human or animal life, and the connection of the imagination borrowed from this aspect of the concepts of diagnosis and cosmetology, as viewed by the Jirjani as one of the most important motives of the rhetoric of metaphor and beauty.- Third: the transfer of mind from one meaning to another through the metaphorical image, and this aspect in two aspects; the text aspect through the textual effects stylistic effects of which the imagination origin.The second is the reception side. The imaginary activity is also the mental process carried out by the recipient during his analysis of the text and textures of the text, and the resulting emotions and responses. This aspect will be separate views of Al-Jarjani. Through our talk about these aspects, clarification of the vision of Al-Jerjani to the concept of imagination in the metaphor.